AGRICULTURE: PROBLEMS AND SUGGESTIONS OF SATHANKULAM TALUK - TUTICORIN DISTRICT - Esakkiammal, M. (International Journal of Research -GRANTHAALAYAH, 2018)
Agriculture is one of the most important pillars of the Indian economy. The contribution of agriculture and its allied sectors to India’s GDP stood at 13.9% during 2013-14. More than half of the Indian population is dependent on agriculture for its subsistence. Since the beginning years of economic development, it has been one of the main drivers of growth of the economy as it supplies was a major source of raw materials to most of the manufacturers. This paper focuses on exploring the socio-economic status of farmer in Tuticorin District, to draw findings, suggestion and conclusion.